Influence of structural load-bearing scaffolds on mechanical load- and BMP-2-mediated bone regeneration. (September 2016) - McDermott, Anna M.; Mason, Devon E.; Lin, Angela S.P.; Guldberg, Robert E.; Boerckel, Joel D.
Abstract: A common design constraint in functional tissue engineering is that scaffolds intended for use in load-bearing sites possess similar mechanical properties to the replaced tissue. Here, we tested the hypothesis that in vivo loading would enhance bone morphogenetic protein-2 (BMP-2)-mediated bone regeneration in the presence of a load-bearing PLDL scaffold, whose pores and central core were filled with BMP-2-releasing alginate hydrogel. First, we evaluated the effects of in vivo mechanical loading on bone regeneration in the structural scaffolds. Second, we compared scaffold-mediated bone regeneration, independent of mechanical loading, with alginate hydrogel constructs, without the structural scaffold, that have been shown previously to facilitate in vivo mechanical stimulation of bone formation. Contrary to our hypothesis, mechanical loading had no effect on bone formation, distribution, or biomechanical properties in structural scaffolds. Independent of loading, the structural scaffolds reduced bone formation compared to non-structural alginate, particularly in regions in which the scaffold was concentrated, resulting in impaired functional regeneration. This is attributable to a combination of stress shielding by the scaffold and inhibition of cellular infiltration and tissue ingrowth. Collectively, these data question the necessity of scaffold similarity to mature tissue at the time of implantation and emphasize development of an environment conducive to cellular activation of matrix production and ultimate functional regeneration. Graphical abstract: Highlights: BMP-2/alginate with and without a structural component are assessed in bone defects. Previously, mechanical loads enhanced non-structural hydrogel-mediated bone repair. inclusion of a structural scaffold prevented mechanical load-induced bone regeneration. Bone formed preferentially in regions not containing structural scaffold. Scaffolds with mechanical similarity to native tissue may inhibit load-induced bone healing.